Interferência e nível de dano econômico de plantas daninhas na cultura da canola - Brandler, Daiani (2019)
The weeds if not controlled compete with crops for the resources of the environment, such water, light and nutrients and consequently causing negative interference on crops if they are not controlled. When weeds appear in high population levels, control is required, however in low infestations it is necessary to quantify the losses of productivity and quality of the product harvested.The interference period of weeds is a tool that helps making decision of the best time to carry out the control so that there is no qualiquantitative reduction of the cultures infested. Some crops have already been developed to estimate the level of economic damage, where weeds are monitored and control measures are applied when it becomes necessary. In this way the objective of this research was to estimate the periods of interference and the level of economic damage of weeds from the canola crop. For this, two experiments were installed in the experimental area of UFFS, Campus Erechim, in the 2017/18 harvest. In the first trial, the period before interference (PAI), the total interference prevention period (PTPI) and the critical interference prevention period (PCPI) of turnip, ryegrass and black oat weeds of the canola cultivar Diamond sown in density of 50 plants m-2, spaced 0.5 m between rows. At 51 days after the emergence of canola, the variables related to morphophysiology, such as photosynthetic rate, internal CO2 concentration, transpiration rate, stomatal conductance of water vapors, carboxylation efficiency, water efficiency, plant height, stem diameter, leaf area, and dry mass of the aerial part of the canola in competition with the weeds. At the time of canola harvest, the yield components of the crop were determined by the number of silica, number of plants per meter and mass of one thousand grains. The experimental design was a randomized block with four replicates, the treatments being separated into two models of interference: in the first, the canola cohabited with weeds for increasing periods of 0, 7, 14, 21, 28, 35 and 42 days after the emergency (DAE) and throughout the cycle; being called the coexistence group and, in the second, the culture was kept free of the infestation for the same periods described previously, called control. In the second trial, the level of economic damage of weeds of the canola hybrids was evaluated; Hyola 50, Hyola 763, Hyola 571 CL, Hyola 575 CL and Diamond seeded at the density of 50 plants m-2, in the same spacing as experiment one. The experimental design was of randomized blocks, without repetition. The variables population of plants, leaf area, soil cover and dry mass of the aerial part of the turnip plants for the calculation of the productivity losses of the canola in the presence of the weed were evaluated. The cost of control (herbicide and tratorized terrestrial application, in dollars ha-1), yield of canola grains (kg ha-1), canola price (kg-1 grains), herbicide efficiency) and the population of turnip plants were used to calculate the level of economic damage of the weed on the crop. The results for the interference period demonstrated that the critical period of interference prevention (PCPI) for canola culture ranges from 25 to 60 DAE. The period prior to interference (PAI) goes up to 25 DAE. And the total interference prevention period (PTPI) is 60 DAEs. The variables: photosynthetic rate, internal CO2 concentration, transpiration rate, stomatal conductance of water vapors, carboxylation efficiency and water efficiency related to the physiology of canola plants were not affected by periods of interference and weed control. The competition of turnip, azevem and black oats in canola negatively altered the morphological variables, plant height, stem diameter, leaf area, number of plants per meter, number of silica, one thousand grain mass and dry mass of the aerial part of the crop. The weed interference reduced the yield of canola by 94.05% when no control method was used. Hyola 575 CL, Hyola 50, Hyola 76 and Hyola 571 CL cane hybrids are more competitive with turnip than hybrids, Hyola 433 and Diamond. The use of hybrids Hyola 50, Hyola 76, Hyola 571 CL and Hyola 575 CL increased the level of economic damage in canola. The values of economic damage levels range from 2.86 to 5.95; 2.43 to 5.05; 2.22 to 5.43 and 2.99 to 6.22 turnip plants m-2 for hybrids Hyola 50, Hyola 76, Hyola 571 CL and Hyola 575 CL, respectively as a function of simulated variables. The increased grain yield, canola price, herbicide efficiency and reduced control cost reduce the level of economic damage, justify the adoption of control measures in smaller turnip populations.